PROBLEMS OF THE RELATIONSHIP BETWEEN DIGITAL TECHNOLOGIES AND SOCIAL DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
This article analyzes the main factors and reasons for the rapid and deep penetration of digital technologies into our lives, as well as the advanced technologies created by developed countries. Also, attention is drawn to the presence of negative features along with its positive effects on the life of people, nations, peoples and countries. In addition, the global changes taking place in the world today, the acceleration of digital technologies, will take the place of mechanical and physical labor in the future.